Ordered mesoporous Co3O4 nanospheres / reduced graphene oxide composites for rutin detection. Issue 7 (May 2018) - Zhang, Jiangjiang; Cui, Shiqiang; Ding, Yaping; Yang, Xinxin; Guo, Kai; Zhao, Jingtai
Abstract: The ordered mesoporous Co3 O4 nanospheres encapsulated with reduced graphene oxide (denoted as meso-Co3 O4 / RGO) were synthesized via electrostatic interaction and firstly for the electrochemical detection of rutin with good sensing effects. The resultant meso-Co3 O4 / RGO nanocatalyst not only possesses more active sites due to the high surface area deriving from the mesoporous structure, but also has benign conductibility due to the presence of RGO, both of which enhance the sensing properties for the electrochemical detection of rutin. The developed sensor displays low detection limit (0.03 μM) and large sensitivity (74.85 μA μM −1 cm −2 ). Besides, the rutin sensor possesses good selectivity, stability and reproducibility. Graphical abstract: fx1